ANTIDIABETIC ACTIVITY OF ANACARDIUM OCCIDENTALE IN ALLOXAN – DIABETIC RATS (Journal of Science and Technology, 2016)
This study investigated the hypoglycemic effect of inner bark extract of Anacardium occidentale Linn. (Anacardiceae) in normal (normoglycemic) and in alloxan-induced diabetic rats. The in- ner reddish bark of the plant was extracted with ethanol and screened for hypoglycemic activity in a model of alloxan-induced diabetes in rat species. Bioactivity-guided fractionation of the ethanolic extract led to fractions that displayed diverse hypoglycemic effects at doses of 34.0, 200.0 and 300.0 mg/kg body weight. The alloxan-diabetic rats showed significant reduction in plasma glucose level after treatment with the fractions. These results lend support to the validity of the folkloric use of A. occidentale in the treatment of diabetes mellitus type II.